Diaquahexa-mu(2)-dichloroacetato-mu(3)-oxido-tetrahydrofurandiiron(III)m anganese(II) - Sadeghi, O.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the oxido-centered title compound, [Fe2Mn(C2HCl2O2)(6)O(C4H8O)(H2O)(2)], the central O atom is linked to three metal atoms, which are themselves each linked to four dichloroacetate anions, and is in a triangular configuration. Two of the metal atoms are each coordinated by a water molecule, whereas the third is coordinated by a tetrahydrofuran molecule. In the crystal, adjacent molecules are linked by O-H center dot center dot center dot O and O-H center dot center dot center dot Cl hydrogen bonds across centers of inversion, generating a hydrogen-bonded chain along the c axis. The Mn-II atoms are disordered with respect to the Fe-III atoms, and the same metal site is occupied by 1/3Mn + 2/3Fe.